2017
DOI: 10.1111/1747-0080.12377
|View full text |Cite
|
Sign up to set email alerts
|

Referrals to dietitians/nutritionists: A cross‐sectional analysis of Australian GP registrars’ clinical practice

Abstract: Established patients with chronic disease and complex care needs are more likely than other patients to be referred by registrars to dietitians/nutritionists. Nutrition behaviours are a major risk factor in chronic disease, and we have found evidence for dietitian/nutritionist referrals representing one facet of engagement by registrars with patients' complex care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…In the general population, time constraints and lack of reimbursement were prominent themes recurrent in previous literature, which prevented GPs from efficiently providing lifestyle management. We report for the first time that similar barriers exist in general practice for PCOS [21,23,24,25,26]. Effective lifestyle counselling requires thorough and longer consultations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the general population, time constraints and lack of reimbursement were prominent themes recurrent in previous literature, which prevented GPs from efficiently providing lifestyle management. We report for the first time that similar barriers exist in general practice for PCOS [21,23,24,25,26]. Effective lifestyle counselling requires thorough and longer consultations.…”
Section: Discussionmentioning
confidence: 93%
“…Despite this, literature reports in the general population that GPs may not be fulfilling this role because of system-related and individual-related factors. These may include poor dissemination of guideline-based information to GPs, lack of funding, competing general practice interests, and time and pressure demands [21,23,24,25,26]. However, the perspective of GPs in providing weight and lifestyle management for women with PCOS has not been addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these attempts appeared to be self-initiated with very little or no support by health professionals [33, 34]. The involvement of a dietitian is unlikely according to the low referral rate of PCOS patient to dietitians, resulting in women with PCOS seeking alternative sources of advice and support for lifestyle modification [34, 35]. It is known that certain behaviour change techniques are essential for successful lifestyle modification [36].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlighted that the registrars’ rate of referral to a dietitian/nutritionist was comparable with that of GPs (Mulquiney et al . ), suggesting that referral for specialist dietary advice is not necessarily ‘front of mind’ for all doctors. If doctors are not directly providing dietary information and are not regularly referring patients to diet specialists, it perhaps is not surprising that information and support are sought from alternative sources such as the media and Internet (Cash et al .…”
Section: Doctors and Nutrition Advice: What Is Happening Now?mentioning
confidence: 99%
“…In an Australian study, Mulquiney et al . () reported that out of 145 708 consultations (by 1124 registrars), there were 227 190 problems/diagnoses and out of these only 587 (0.26%) resulted in a referral to a dietitian/nutritionist. The most common conditions for prompting a referral were obesity and type 2 diabetes.…”
Section: Doctors and Nutrition Advice: What Is Happening Now?mentioning
confidence: 99%